2011
DOI: 10.1111/j.1740-8709.2011.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of inappropriate timing of introducing solid, semi‐solid or soft food to infants in Pakistan: Secondary data analysis of Demographic and Health Survey 2006–2007

Abstract: Inappropriate timing of introducing complementary food deprives the infant of optimum nutrition, leading to undernutrition, and increased mortality and morbidity. The aim of this analysis was to identify determinants of inappropriate timing of introduction of solid, semi-solid and soft foods in Pakistan. Data on 941 infants 3.00 to 8.99 months were obtained from the Pakistan Demographic and Health Survey 2006-2007. The prevalence of introduction of foods among infants aged 3.00-5.99 months and 6.00-8.99 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
7
42
2
1
Order By: Relevance
“…Children from a family size, containing four and more members, were 71.3% less likely to get appropriate weaning than those from family size of three and less. This finding is in line with findings of EDHS 2011 [12] and a study done in Pakistan [25], which conclude that the second and third born children had a higher risk of not gaining weaning foods in the recommended age than those of first born infants. This might be related to food affordability problem with increased family size.…”
Section: Discussionsupporting
confidence: 91%
“…Children from a family size, containing four and more members, were 71.3% less likely to get appropriate weaning than those from family size of three and less. This finding is in line with findings of EDHS 2011 [12] and a study done in Pakistan [25], which conclude that the second and third born children had a higher risk of not gaining weaning foods in the recommended age than those of first born infants. This might be related to food affordability problem with increased family size.…”
Section: Discussionsupporting
confidence: 91%
“…Regional differences in the rates of EISF have been reported in Pakistan [36]. Although this finding was not revealed for Ghana in this study, rates of EISF were found to vary in the geographical regions in Liberia, Nigeria and Senegal.…”
Section: Discussioncontrasting
confidence: 71%
“…This is in line with previous studies from south east Asian contexts that show a positive association of a child’s nutritional intake with mother’s educational status [13, 44, 45, 47, 48]. Analysis of the Indian National Family Health Survey has similarly found mothers education (and household income) to be important predictors of child feeding practices [48].…”
Section: Discussionsupporting
confidence: 89%
“…We found no statistically significant difference between minimal acceptable diet by child gender, which echoes the findings of other studies on child feeding in South Asia [13, 44, 45]. However, given high levels of male child preference in the region, we expected boys to be significantly more likely to receive minimum acceptable diet than girls, when in fact our (non-significant) findings show that girls were more likely to receive minimum acceptable diet than boys.…”
Section: Discussionsupporting
confidence: 83%